Epidemiological profile of type 1 diabetes among primary school children in Baghdad, Iraq - Zalzala, Sarah Haider; Al-Lami, Faris H.; Fahad, Khalid Saeed (Journal of Contemporary Medical Sciences, 2020)
Objectives: To estimate the prevalence of type 1 Diabetes Mellitus in primary school children in Baghdad City, and to evaluate its effect on growth of those children. Methods: This comparative cross-sectional study was conducted in a sample of primary schools in Baghdad city selected by multistage cluster sampling. All primary school students in the selected schools were included. For every diabetic child, we selected a child from the same class who is free from diabetes. Information on disease variables were obtained through sending questionnaire to the children’s parents. The Centers for Disease Control and Prevention growth charts were used. Results: The total number of primary school students in the selected 141 schools was 69,115; 110 of them had T1DM (159/100,000). Female to male ratio was 1.3:1. Obesity and underweight were significantly lower in diabetics than non-diabetic children (P=0.03). Conclusion: The prevalence of type 1 diabetes mellitus was 159 per 100,000, which was approximate to the prevalence in Saudi Arabia, less than that in Al-Kuwait, but higher than that in Turkey. Percentage of underweight and obesity were lower in the diabetics while overweight percentage was slightly higher compared to the non-diabetics.